(untitled) (Research, Society and Development, 2021)
In the last decades, the eCB system has been highlighted by its neuro and immunomodulatory effects. Beyond CB1R effects in Central Nervous System (CNS), CB2R target drugs has been showed to be promising to mitigation of neuroinflammatory diseases in mouse models. However, it remains unknow the effects of CB2R target drugs on behavior. Therefore, we review the effects of CB2R on behavior in murine models by Pubmed website, selecting studies between 2001 to 2021. In this sense, many studies has demonstrated the effects of overexpression, lack, activation or antagonization of CB2R on Aggressive behavior, Memory-associated behaviors, Mood disorders and Reward behavior. Similarly, it is not clear yet how the eCB system modulates the behavior through CB2Rs present in neurons. Thus, in mouse models, although the pharmacological treatment with CB2R target drugs seems to be promising for neuroinflammatory diseases, on behavior there are few answers about the pathways of this modulation, as well as, it is fundamental the development and/or the update of behavioral tests that evaluate many parameters, then expose better interpretations in these tests.